The prevalence of the signs and symptoms of the temporomandibular joint dysfunction in Filipino osteoarthritis patients in the Philippine General Hospital - Concio, Melissa B.
The temporomandibular joint dysfunction (TMD) has been considered multifactorial. One of the suggested etiologic factors is the degenerative joint disease or “osteoarthritis” (OA). Several international studies suggested a positive association between the two, proposing that the degenerative changes that occur in such joint problems may result to symptoms of joint dysfunction, such as the TMD. Such occurrence in the TMJ raised a question ofwhether the prevalence ofthe signs and symptoms in osteoarthritic patients is significant enough to imply a relationship between the two disorders. This study aimed to answer this problem in a local situation through questionnaire-interview and clinical examination of the TMJ of 30 OA patients (case group) diagnosed in the OPD-PGH and 30 non-OA volunteers (control group). The data gathered were subjected to the T-test and analysis of the extraneous factors, such as the patients’ medical profile, dental status, different pain perceptions, and iatrogenic factors. The results of this study showed that the differences in the mean numbers and proportions of the signs and symptoms of TMD in the selected OA patients and non-OA patients were statistically significant which implies a greater probability that OA patients are more prone to manifest the signs and symptoms of TMD than those -without osteoarthritis. However, upon consideration of the contributory factors mentioned above, the findings of this study cannot be generalized and applied to the whole osteoarthritic population.